Method for degrading high polymer material containing carbon-carbon double bonds
By initiating the carbonyl-double bond metathesis reaction with iron-based Lewis acid catalyst, the problems of high degradation costs of polymer materials and harmful to organisms in the prior art are solved, and efficient, low-cost and environmentally friendly polymer materials are achieved.
Patent Information
- Application Number
- CN202510011370.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The prior art is difficult to achieve efficient, low-cost and environmentally friendly degradation of polymer materials, especially on industrial scale, and traditional catalysts are expensive and harmful to organisms.
The iron-based Lewis acid catalyst is used to efficiently degrade polymers by initiating the carbonyl-double bond metathesis reaction, which is low-cost, simple in structure, high in activity, and is beneficial to organisms.
It achieves efficient degradation of polymer materials, adjustable product components, and can use products, with high degradation efficiency and low cost, which is suitable for industrial-scale applications.
Smart Images

Figure CN119822936A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer degradation, and particularly relates to a method for degrading a polymer material containing carbon-carbon double bonds. Background Art
[0002] Polyolefin materials based on petrochemical industry are widely present in chemical industry and daily production and life, such as widely used rubber, plastic, elastomer and fiber, among which there are bulk polyolefin materials such as polyethylene and polypropylene, and also include materials such as EPDM and EPDM, which are obtained through coordination polymerization. However, it is completely composed of CH and CC chemical bonds, which are extremely difficult to break and degrade under natural conditions. For example, linear low-density polyethylene (LLDPE, ethylene-α-olefin random copolymer) used for disposable packaging bags or agricultural films, it is often only a few months or even a few days from production to abandonment, and it takes 100-200 years to be completely degraded in the natural environment. The large-scale use of polyolefin materials, in addition to bringing convenience to people's lives, has brought huge burdens to the environment by being discarded in large quantities after use.
[0003] Every year, 30-40 million tons of plastic products such as packaging bags, coating films, pipes, containers, etc. are abandoned. Due to their inert chemical properties, they are difficult to degrade and disappear in geological and marine environments. Plastic waste in the ocean and the ecological hazards it brings have long attracted widespread attention from the international community. According to statistics, the weight of plastic waste such as polyolefins and polyesters discarded into the ocean every year reaches tens of millions of tons. These wastes are difficult to collect again, which brings great challenges to environmental governance. Since it is difficult to degrade naturally and the demand will exist for a long time or even increase, it is very necessary to study its effective artificial degradation treatment.
[0004] Currently, the more advanced degradation methods include introducing degradable ester groups and carbon-carbon double bonds into the main chain of such polymer molecules. Among them, the method of breaking the carbon-carbon double bond only revolves around the olefin metathesis reaction, using expensive ruthenium-based or palladium-based catalysts to break it and convert it into small molecules or low molecules. At the same time, such catalysts need to be used in more stringent reaction or production environments, such as anhydrous and oxygen-free conditions. At the same time, catalysts based on ruthenium or palladium are relatively expensive (such as Grubbs catalyst, etc.), which are not suitable for industrial mass production; some catalysts have more residues in the degradation products, such as ruthenium or palladium salts, which are harmful to organisms and cannot be used on a large scale for large-scale low-cost degradation of recycled polymer materials, thus limiting the widespread application of such methods.
[0005] Therefore, there is an urgent need for a convenient, cheap, and fast method for decomposing and recycling polymer materials that can be applied on a large scale. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a method for degrading polymer materials containing carbon-carbon double bonds. The present invention uses an iron-based Lewis acid catalyst to efficiently induce the degradation of polymers, has low cost, simple structure, high activity, is very convenient to use, and is beneficial to organisms; the principle of initiating carbonyl-double bond metathesis reaction is simple and easy to operate, and polymerization can be carried out at room temperature. The product composition can be regulated according to the selected aldehyde-containing or ketone-containing reagent, and the product can be used and has high utilization value.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for degrading a polymer material containing carbon-carbon double bonds, comprising the following steps:
[0009] Dissolving a polymer material containing a carbon-carbon double bond in a halogenating agent to obtain a polymer material solution;
[0010] The polymer material solution, the catalyst, and the aldehyde or ketone group-containing reagent are mixed and reacted sufficiently to obtain a degradation solution, thereby completing the degradation;
[0011] The catalyst is an iron-based Lewis acid.
[0012] Preferably, the concentration of the polymer material solution is 5-10 mg / mL.
[0013] Preferably, the polymer material containing carbon-carbon double bonds includes but is not limited to polybutadiene, polyisoprene, copolymers of ethylene or propylene with butadiene or isoprene and other comonomers, polymers obtained by ring-opening polymerization of cyclooctadiene, styrene-butadiene diblock or triblock copolymers, and polymers containing carbon-carbon double bonds obtained by dehydrogenating polyethylene or polypropylene by a dehydrogenation reaction.
[0014] Preferably, the halogenating agent is one or more of dichloromethane, dichloroethane, chloroform, carbon tetrachloride, chlorobenzene, dichlorobenzene, trichlorobenzene and tetrachloroethane.
[0015] Preferably, the molar ratio of the catalyst to the carbon-carbon double bonds in the polymer material containing carbon-carbon double bonds is (1-10):100.
[0016] Preferably, the iron-based Lewis acid is an iron halide or iron trifluoromethanesulfonate; further preferably, it is iron trifluoride, iron trichloride, iron tribromide, iron (II) trifluoromethanesulfonate, or iron (III) trifluoromethanesulfonate; the above iron-based Lewis acids degrade carbon-carbon double bond-containing polymers by following the carbonyl-double bond metathesis mechanism and the [2+2] cycloaddition-cycloconversion mechanism, and the polymer chain segments and small molecules are ectopically converted into low molecular weight products.
[0017] Preferably, the molar ratio of the aldehyde or ketone group-containing reagent to the carbon-carbon double bonds in the carbon-carbon double bond-containing polymer material is (1-5):1.
[0018] Preferably, the aldehyde or ketone-containing reagent includes, but is not limited to, one or more of benzaldehyde, benzophenone, benzophenone, butyrophenone, formaldehyde or acetone. By adopting the above technical solution, the product composition can be regulated according to the selected aldehyde or ketone-containing reagent.
[0019] Preferably, the reaction temperature can be selected according to the polymer material containing carbon-carbon double bonds; the reaction temperature is 23 to 80° C., and the reaction time is 3 to 24 hours.
[0020] Preferably, after the polymer material containing carbon-carbon double bonds is completely degraded, a recovery step is further included, and the specific method of the recovery step is:
[0021] The degradation solution is quenched by removing iron salt using rapid silica gel column chromatography to obtain a quenching solution;
[0022] The quenching solution is then dropped into methanol for precipitation to remove macromolecular substances, and the methanol solution is then collected by filtration. The methanol solution is then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as an eluent to obtain a small molecule reagent.
[0023] Beneficial technical effects:
[0024] (1) The present invention uses an iron-based Lewis acid catalyst to efficiently induce the degradation of high molecular weight polymers, which is low in cost, simple in structure, highly active, very convenient to use, and beneficial to organisms; the principle of initiating the carbonyl-double bond metathesis reaction is simple and easy to operate, and polymerization can be carried out at room temperature. The product composition can be regulated according to the selected aldehyde- or ketone-containing reagents, and the product is usable and has high utilization value.
[0025] (2) The present invention only requires heating the insoluble polymer to the dissolution temperature in the original step; optionally, the degradation of the polymer containing carbon-carbon double bonds can be initiated at room temperature or at elevated temperature, and the degradation of the polymer material can be completed by directly mixing the existing reaction reagents and reacting for a certain period of time.
[0026] (3) In the reaction at room temperature of the present invention, the amount of catalyst used can be as low as 1 mol% (relative to the molar amount of carbon-carbon double bonds in the polymer), and the iron-based catalyst can be stored in a state of being exposed to dry air and can be stored in an atmosphere of a non-inert gas (such as nitrogen, helium, etc.) (deterioration is less than 1% by weight after 12 months), which has the advantages of convenient storage and transportation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1The carbon NMR spectrum of the degradation product of Example 1 is shown in FIG.
[0028] Figure 2 The following is the H NMR spectrum of the degradation product of Example 2.
[0029] Figure 3 The carbon NMR spectrum of the degradation product of Example 3 is shown.
[0030] Figure 4 The following is the H NMR spectrum of the degradation product of Example 4.
[0031] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of the degradation product of Example 10.
[0032] Figure 6 This is the gel permeation chromatography (GPC) curve of the raw material starting polymer.
[0033] Figure 7 It is the gel permeation chromatography (GPC) curve diagram of the degradation products of Examples 1 to 5.
[0034] Figure 8 This is the H NMR spectrum of the degradation product 5-phenyl-4-pentenal.
[0035] Fig. 9 This is the H NMR spectrum of the degradation product 6-phenyl-5-hexen-2-one.
[0036] Fig.10 This is the mass spectrum of the degradation product 5-phenyl-4-pentenal.
[0037] Fig.11 This is the mass spectrum of the degradation product 6-phenyl-5-hexen-2-one.
[0038] Fig.12 This is the hydrogen nuclear magnetic resonance spectrum of the degradation product of Example 19. DETAILED DESCRIPTION
[0039] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0040] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] In the following examples, room temperature refers to 23° C., and the raw materials used are all commercially available conventional raw materials, without any special limitation. The following description will not be repeated.
[0045] Example 1
[0046] Trans-poly 1,4-butadiene (molecular weight 26.1kDa, molecular weight distribution ) is a highly crystalline polymer with a melting point of over 130°C. Even at a concentration of 10 mg / mL, it is not easily dissolved in a solvent at room temperature (RT, 23°C). Therefore, it was dissolved in dichloroethane at 80°C (concentration of 5 mg / mL). Specifically, in a 250mL three-necked round-bottom flask equipped with a stirring bar, a halogenating agent (150mL) and trans-poly (1,4-butadiene) (0.75g, 13.9mmol butadiene unit) were added and heated to 80°C under nitrogen. After the polymer was completely dissolved, benzaldehyde (7.37g) was added, followed by ferric chloride (225mg, 10mol% of butadiene units). The mixture was stirred to dissolve. The resulting reaction was allowed to proceed at 80°C for 3 hours and then cooled to room temperature. It was quenched by removing the iron salt using flash silica gel column chromatography. Subsequently, the solution was dropped into methanol to precipitate the macromolecule. The soluble components were collected by removing methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluent. A pale yellow solid (0.30 g, degradation efficiency 60%) was obtained by precipitation from methanol. The NMR carbon spectrum of the degradation product is shown in Figure 1 As shown, product structure information: 1H NMR (400MHz, 1,2-dichlorobenzene-d4, ppm): δ = 5.63 (m, 2H), 2.24 (m, 4H). 13 C NMR (101MHz, 1,2-dichlorobenzene-d4, ppm): δ=130.05, 32.6. Gel permeation chromatography (GPC) (1,2,4-trichlorobenzene, polystyrene standard): M n =3.2 kDa, The small molecules dissolved in methanol are mainly 5-phenyl-4-pentenal, product structure information: 1 H NMR (400MHz, Chloroform-d) δ = 9.80 (t, J = 1.5 Hz, 1H), 7.40-7.13 (m, 5H), 6.42 (dt, J = 15.9, 1.5 Hz, 1H), 6.19 (dt, J = 15.8, 6.6 Hz, 1H), 2.70-2.43 (m, 4H). Mass spectrum information: HRMS: [M+H] + calcdfor C 11 H 13 O:161.2122,found:161.1972.
[0047] Example 2
[0048] In a 250mL three-necked round-bottom flask equipped with a stirring bar, cis-poly(1,4-butadiene) (1g, 18.5mmol butadiene units) (molecular weight 135.2kDa, molecular weight distribution D=1.8) was dissolved in 100mL dichloromethane at room temperature under N2 at a concentration of 10mg / mL. Subsequently, benzaldehyde (1.55g, 1 equivalent of butadiene units) and ferric chloride (300mg, 10 mol% butadiene units) were added. The resulting reaction was allowed to proceed at room temperature for 12 hours. The iron salt was removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. A sticky solid precipitant (0.22g, degradation efficiency 78%) was obtained from methanol, and the nuclear magnetic resonance carbon spectrum of the degradation product is shown in the following figure: Figure 2 As shown, product structure information: H NMR spectrum, 1 H NMR (400MHz, Chlorofor md), δ=5.52-5.27(m,2H), 2.18-1.93(m,4H). 13C NMR (101 MHz, CDC 13, ppm): δ = 129.61, 27.42. Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =3.1 kDa, The small molecules dissolved in methanol are mainly 5-phenyl-4-pentenal, product structure information: 1 H NMR (400MHz, Chloroform-d) δ = 9.81 (t, J = 1.5 Hz, 1H), 7.40-7.13 (m, 5H), 6.43 (dt, J = 15.9, 1.5 Hz, 1H), 6.19 (dt, J = 15.8, 6.6 Hz, 1H), 2.71-2.44 (m, 4H). Mass spectrum information: HRMS: [M+H] + Calculate for C 11 H 13 O:161.2109,found:161.0882.
[0049] Example 3
[0050] In a 500 mL three-necked round-bottom flask equipped with a stirring bar, trans-poly(1,4-isoprene) (1 g, 14.7 mmol isoprene units) (molecular weight 116.4 kDa, molecular weight distribution ) was dissolved in 200 mL of dichloroethane at a concentration of 5 mg / mL. Subsequently, benzaldehyde (7.8 g, 5 equivalents of butadiene units) and ferric tribromide (434 mg, 10 mol% isoprene units) were added. The resulting reaction was allowed to proceed at room temperature for 24 hours. The iron salt was removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing the methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. The precipitant obtained from methanol was a viscous solid (0.31 g, degradation efficiency 69%), and the nuclear magnetic resonance carbon spectrum of the degradation product was shown as follows Figure 3 As shown, product structure information: H NMR spectrum, 1 H NMR (400MHz, Chloroform-d), δ = 5.22-5.00 (m, 2H), 2.17-1.87 (m, 4H), 1.60 (d, J = 1.3Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 134.96, 124.26, 39.77, 26.75, 16.05. Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =4.7 kDa, The small molecules dissolved in methanol are mainly 6-phenyl-5-hexen-2-one. The product structure information is: 1 H NMR (400MHz, Chloroform-d) δ = 7.39-7.11 (m, 5H), 6.40 (dt, J = 15.8, 1.5Hz, 1H), 6.19 (dt, J = 15.8, 6.8Hz, 1H), 2.69-2.40 (m, 4H), 2.16 (s, 3H). Mass spectrum information: HRMS: [M+H] + Calculate for C 12 H 15 O:175.2033,found:175.1977.
[0051] Example 4
[0052] In a 500 mL three-necked round-bottom flask equipped with a stir bar, cis-poly(1,4-isoprene) (1 g, 14.7 mmol isoprene units) (molecular weight 145.1 kDa, molecular weight distribution ) was dissolved in 200 mL of chloroform at a concentration of 5 mg / mL. Subsequently, benzaldehyde (3.1 g, 2 equivalents of isoprene units) and iron (III) trifluoromethanesulfonate (739 mg, 10 mol% isoprene units) were added. The resulting reaction was allowed to proceed at room temperature for 6 hours. The iron salt was removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing the methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. The precipitant obtained from methanol was a viscous solid (0.15 g, degradation efficiency 85%), and the nuclear magnetic resonance carbon spectrum of the degradation product was shown as follows Figure 4 As shown, product structure information: H NMR spectrum, 1 H NMR (400MHz, Chloroform-d), δ = 5.12 (d, J = 1.6Hz, 2H), 2.11-1.98 (m, 4H), 1.68 (d, J = 1.4Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 135.22, 125.03, 32.21, 26.40, 23.44. Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =3.7 kDa, The small molecules dissolved in methanol are mainly 6-phenyl-5-hexen-2-one. The product structure information is: 1H NMR (400MHz, Chloroform-d) δ = 7.40-7.11 (m, 5H), 6.42 (dt, J = 15.8, 1.5Hz, 1H), 6.18 (dt, J = 15.8, 6.8Hz, 1H), 2.68-2.40 (m, 4H), 2.17 (s, 3H). Mass spectrum information: HRMS: [M+H] + Calculate for C 12 H 15 O:175.2019,found:175.1039.
[0053] Example 5
[0054] In a 250 mL three-necked round-bottom flask equipped with a stirring bar, cis-poly(1,4-butadiene) (1 g, 18.5 mmol butadiene units) (molecular weight 135.2 kDa, molecular weight distribution ) was dissolved in 100 mL of dichloroethane at a concentration of 10 mg / mL. Subsequently, benzophenone (8.4 g, 2.5 equivalents of butadiene units) and iron trifluoride (209 mg, 10 mol% butadiene units) were added. The resulting reaction was allowed to proceed at room temperature for 12 hours. The iron salt was removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. A solid precipitate (0.20 g, degradation efficiency 80%) was obtained from methanol, and the product structure information: H NMR spectrum, 1 H NMR (400MHz, Chloroform-d), δ=5.52-5.28(m,2H), 2.18-1.94(m,4H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 129.62, 27.44. Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =2.8 kDa, The small molecules dissolved in methanol are mainly 5,5-diphenyl-4-pentenal, product structure information: 1 H NMR (400MHz, Chloroform-d) δ = 9.80 (t, J = 1.5 Hz, 1H), 7.40-7.14 (m, 10H), 6.25 (dt, J = 15.8, 6.6 Hz, 1H), 2.70-2.45 (m, 4H). Mass spectrum information: HRMS: [M+H] + Calculate for C 17 H 17O:237.2104,found:237.2011.
[0055] Example 6
[0056] In a 500 mL three-necked round-bottom flask equipped with a stir bar, cis-poly(1,4-isoprene) (1 g, 14.7 mmol isoprene units) (molecular weight 145.1 kDa, molecular weight distribution ) was dissolved in 200 mL of dichloroethane at a concentration of 5 mg / mL. Subsequently, acetone (4.3 g, 5 equivalents of isoprene units) and iron (III) trifluoromethanesulfonate (30 mg, 1 mol% isoprene units) were added. The resulting reaction was allowed to proceed at room temperature for 12 hours. The iron salts were removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing the methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. The precipitant obtained from methanol was a viscous solid (0.25 g, degradation efficiency 75%), product structure information: H NMR spectrum, 1 H NMR (400MHz, Chloroform-d), δ = 5.11 (d, J = 1.6Hz, 2H), 2.11-1.99 (m, 4H), 1.67 (d, J = 1.4Hz, 3H). 13 CNMR (101MHz,CDCl3,ppm):δ=135.21,125.02,32.21,26.41,23.43. Gel permeation chromatography (GPC) (THF,polystyrene standard):M n =3.8 kDa, The small molecules dissolved in methanol are mainly 6-methyl-5-heptene-2-one. Product structure information: 1 H NMR (400MHz, Chloroform-d) δ = 6.42 (dt, J = 15.8, 1.5 Hz, 1H), 6.26 (dt, J = 15.8, 6.8 Hz, 1H), 2.65-2.45 (m, 4H), 1.77 (s, 6H). Mass spectrum information: HRMS: [M+H] + cal cd for C8H 15 O:127.2018,found:127.1987.
[0057] Example 7
[0058] In a 250 mL three-necked round-bottom flask equipped with a stirring bar, cis-poly(1,4-butadiene) (1 g, 18.5 mmol butadiene units) (molecular weight 135.2 kDa, molecular weight distribution ) was dissolved in 100 mL of tetrachloroethane at a concentration of 10 mg / mL. Subsequently, acetophenone (6.7 g, 3 equivalents of butadiene units) and iron (II) trifluoromethanesulfonate (327 mg, 5 mol% butadiene units) were added. The resulting reaction was allowed to proceed at room temperature for 12 hours. The iron salts were removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing the methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. A solid precipitate (0.20 g, degradation efficiency 80%) was obtained from methanol, and the product structure information: H NMR spectrum, 1 H NMR (400MHz, Chloroform-d), δ=5.53-5.28(m,2H), 2.18-1.95(m,4H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 129.61, 27.45. Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =4.1kDa, The small molecules dissolved in methanol are mainly 5-phenyl-4-hexenal, product structure information: 1 H NMR (400MHz, Chloroform-d) δ = 9.74 (t, J = 1.5 Hz, 1H), 7.40-7.12 (m, 5H), 5.79 (dt, J = 15.8, 6.6 Hz, 1H), 2.71-2.44 (m, 4H), 2.13 (dt, 3H). Mass spectrum information: HRMS: [M+H] + Calculate for C 12 H 15 O:175.2094,found:175.2013.
[0059] Example 8
[0060] In a 250 mL three-necked round-bottom flask equipped with a stir bar, cis-poly(1,4-isoprene) (1 g, 14.7 mmol isoprene units) (molecular weight 145.1 kDa, molecular weight distribution ) was dissolved in 100 mL of dichlorobenzene at a concentration of 10 mg / mL. Subsequently, formaldehyde (2.2 g, 5 equivalents of isoprene units) and ferric chloride (238 mg, 10 mol% isoprene units) were added. The resulting reaction was allowed to proceed at room temperature for 12 hours. The iron salts were removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. The precipitant obtained from methanol was a viscous solid (0.25 g, degradation efficiency 75%), product structure information: H NMR spectrum, 1 H NMR (400MHz, Chloroform-d), δ=5.12 (d, J=1.6Hz, 2H), 2.11-1.98 (m, 4H), 1.67 (d, J=1.4Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 135.20, 125.02, 32.22, 26.41, 23.44. Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =3.8 kDa, The small molecules dissolved in methanol are mainly 5-hexen-2-one, product structure information: 1 H NMR (400MHz, Chloroform-d) δ = 5.82 (dt, J = 15.8, 1.5 Hz, 1H), 5.26 (dt, J = 15.8, 6.8 Hz, 2H), 2.45 (m, 4H), 2.10 (s, 3H). Mass spectrum information: HRMS: [M+H] + Calculation for C6H 11 O:99.2019,found:99.1997.
[0061] Example 9
[0062] In a 500mL three-necked round-bottom flask equipped with a stirring bar, cis-poly(1,4-isoprene) (1 g, 14.7 mmol isoprene units) (molecular weight 145.1 kDa, molecular weight distribution D = 2.2) was dissolved in 200mL trichlorobenzene at a concentration of 5 mg / mL under N2 at room temperature. Subsequently, phenylbutyl ketone (4.4 g, 2 equivalents of isoprene units) and ferric chloride (238 mg, 10 mol% isoprene units) were added. The resulting reaction was allowed to proceed at room temperature for 24 hours. The iron salt was removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluent. The precipitant obtained from methanol was a solid precipitate (0.13 g, degradation efficiency 87%), product structure information: nuclear magnetic resonance hydrogen spectrum, 1 H NMR (400MHz, Chloroform-d), δ = 5.11 (d, J = 1.6Hz, 2H), 2.12-1.98 (m, 4H), 1.68 (d, J = 1.4Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 135.22, 125.02, 32.22, 26.42, 23.44. Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =3.8 kDa, The small molecules dissolved in methanol are mainly 6-phenyl-5-nonen-2-one, product structure information: 1 H NMR (400 MHz, Chloroform-d) δ = 7.39-7.11 (m, 5H), 5.78 (dt, J = 15.8, 1.5 Hz, 1H), 2.24 (m, 4H), 2.15 (s, 3H), 1.94 (m, 2H), 1.36 (m, 2H), 0.97 (s, 3H). Mass spectrum information: HRMS: [M+H] + Calculate for C 15 H 21 O:217.2018,found:217.1987.
[0063] Example 10
[0064] In a 250 mL three-necked round-bottom flask equipped with a stirring bar, styrene-butadiene triblock copolymer SBS (1 g, 70 wt% butadiene segment, 13.0 mmol butadiene unit) (molecular weight 110.4 kDa, molecular weight distribution ) was dissolved in 100 mL of dichloroethane at a concentration of 10 mg / mL. Subsequently, benzaldehyde (4.1 g, 3 equivalents of butadiene units) and ferric chloride (211 mg, 10 mol% butadiene units) were added. The resulting reaction was allowed to proceed at room temperature for 12 hours. The iron salt was removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. A solid precipitate (0.35 g) was obtained from methanol, and the product (polystyrene) and the H NMR spectrum of the styrene-butadiene triblock copolymer SBS before and after degradation were shown in Figure 2. Figure 5 shown.
[0065] Product structure information: H NMR spectrum, 1 H NMR (400 MHz, Chloroform-d), δ=7.15-6.07 (m, 5H), 2.25-0.91 (m, 3H). Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =15.2kDa, The small molecules dissolved in methanol are mainly 5-phenylpent-4-enal, product structure information: 1 H NMR (400MHz, Chloroform-d) δ = 9.80 (t, J = 1.5 Hz, 1H), 7.40-7.14 (m, 5H), 6.43 (dt, J = 15.9, 1.5 Hz, 1H), 6.18 (dt, J = 15.8, 6.6 Hz, 1H), 2.70-2.44 (m, 4H). Mass spectrum information: HRMS: [M+H] + calcdfor C 11 H 13 O:161.2102,found:161.1967.
[0066] Embodiment 11
[0067] In a 250 mL three-necked round-bottom flask equipped with a stirring bar, a copolymer poly(ethylene-isoprene-1-hexene) (1 g, 0.76 mol% isoprene units, 0.56 mmol isoprene units) (molecular weight 114.1 kDa, molecular weight distribution ) was dissolved in 100 mL of dichloroethane at a concentration of 10 mg / mL. Subsequently, benzaldehyde (27 mg, 5 equivalents of butadiene units) and ferric chloride (9 mg, 10 mol% butadiene units) were added. The resulting reaction was allowed to proceed at room temperature for 12 hours. The iron salts were removed by using rapid silica gel column chromatography, and the solution was dropped into methanol to precipitate the macromolecules. The soluble components were collected by removing methanol, and then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluents. A solid precipitate (0.96 g) was obtained from methanol, and the product structure information: H NMR spectrum, 1 H NMR (400 MHz, Chloroform-d), δ=1.39-1.07 (m), 0.81 (s). Gel permeation chromatography (GPC) (THF, polystyrene standard): M n =3.5 kDa, The small molecules dissolved in methanol should be mainly 6-phenyl-5-hexen-2-one, which has very little yield and cannot be collected and characterized.
[0068] The degradation methods of Examples 12 to 20 were carried out with reference to Example 2. The raw materials and degradation efficiency are shown in Table 1.
[0069] Table 1
[0070]
[0071]
[0072]
[0073] Experimental Example 1
[0074] The gel permeation chromatography (GPC) curve of the starting polymer is as follows: Figure 6 As shown, curve a is cis-poly 1,4-butadiene; curve b is styrene-butadiene triblock copolymer SBS; curve c is cis-poly 1,4-isoprene; curve d is copolymer poly (ethylene-isoprene-1-hexene).
[0075] The gel permeation chromatography (GPC) curves of the degradation products of Examples 1 to 5 are as follows: Figure 7 As shown, curve 1 is the degradation product of Example 1; curve 2 is the degradation product of Example 2; curve 3 is the degradation product of Example 3; curve 4 is the degradation product of Example 4; and curve 5 is the degradation product of Example 5.
[0076] The H NMR spectrum of the degradation product 5-phenyl-4-pentenal is as follows: Figure 8 shown.
[0077] The H NMR spectrum of the degradation product 6-phenyl-5-hexen-2-one is as follows: Fig. 9 shown.
[0078] The mass spectrum of the degradation product 5-phenyl-4-pentenal, such as Fig.10 shown.
[0079] The mass spectrum of the degradation product 6-phenyl-5-hexen-2-one is as follows: Fig.11 shown.
[0080] The H NMR spectrum of the poly(ethylene-isoprene) degradation product in Example 19 is as follows: Fig.12 shown.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for degrading a polymer material containing carbon-carbon double bonds, characterized in that: The following steps are involved: Dissolving a polymer material containing a carbon-carbon double bond in a halogenating agent to obtain a polymer material solution; The polymer material solution, the catalyst, and the aldehyde or ketone group-containing reagent are mixed and reacted sufficiently to obtain a degradation solution, thereby completing the degradation; The catalyst is an iron-based Lewis acid.
2. The method according to claim 1, characterized in that The concentration of the polymer material solution is 5-10 mg / mL.
3. The method according to claim 1, characterized in that The polymer material containing carbon-carbon double bonds includes, but is not limited to, polybutadiene, polyisoprene, copolymers of ethylene or propylene with butadiene or isoprene and other comonomers, polymers obtained by ring-opening polymerization of cyclooctadiene, styrene-butadiene diblock or triblock copolymers, and polymers containing carbon-carbon double bonds obtained by dehydrogenating polyethylene or polypropylene through a dehydrogenation reaction.
4. The method according to claim 1, characterized in that: The halogenating agent is one or more of dichloromethane, dichloroethane, chloroform, carbon tetrachloride, chlorobenzene, dichlorobenzene, trichlorobenzene and tetrachloroethane.
5. The method according to claim 1, characterized in that The molar ratio of the catalyst to the carbon-carbon double bonds in the high molecular material containing carbon-carbon double bonds is (1-10):
100.
6. The method according to claim 1, characterized in that The iron-based Lewis acid is iron halide or iron trifluoromethanesulfonate.
7. The method according to claim 1, characterized in that The molar ratio of the aldehyde or ketone group-containing reagent to the carbon-carbon double bond in the high molecular material containing the carbon-carbon double bond is (1-5):
1.
8. The method according to claim 1, characterized in that The aldehyde or ketone-containing reagent includes, but is not limited to, one or more of benzaldehyde, benzophenone, benzophenone, butyrophenone, formaldehyde or acetone.
9. The method according to claim 1, characterized in that: The reaction temperature can be selected according to the polymer material containing carbon-carbon double bonds; the reaction temperature is 23-80° C., and the reaction time is 3-24 hours.
10. The method according to claim 1, characterized in that After the polymer material containing carbon-carbon double bonds is completely degraded, a recovery step is also included. The specific method of the recovery step is: The degradation solution is quenched by removing iron salt using rapid silica gel column chromatography to obtain a quenching solution; The quenching solution is then dropped into methanol for precipitation to remove macromolecular substances, and the methanol solution is then collected by filtration. The methanol solution is then separated and purified by silica gel column chromatography using petroleum ether / ethyl acetate as an eluent to obtain a small molecule reagent.
Citation Information
Patent Citations
Methods and materials for depolymerizing polyesters
CN105658611A
Method for forming an aromatic diacid and / or an aromatic diacid precursor from a polyester-containing feedstock
CN105873895A
Method for preparing chemicals by degrading unsaturated polyester resin material in aqueous phase system
CN113831588A
Process for selective catalytic hydrogenation of dienones
CN119212972A
Process for minimizing formation of low molecular weight oligomers during hydrolytic depolymerization of condensation polymers
US4578510A